Pengaruh Profitabilitas, Kepemelikan Konstitusional, Pajak dan Kualitas Good Corporate Governance Terhadap Manajemen Laba ( Studi Empiris pada Perusahaan Go Public yang Terdaftar dalam Penliaian IICG pada Tahun 2011-2013) - Putro, Alif Romadhon, Dr. Triyono, S.E., M.Si (2016)
The research almed to analyze the influence of profitability, ownership of institusional, tax, and good corporate governance quality to earning management. The object of study are all of go public companies listed in IICG period 2011 - 2013 . The population used in this study are all of go public companies listed in IICG period 2011 -2013. The study used purposive sampling method to collcet the sample.The number of sampel collected as many companies with 52 data .The collecter data were analyzed using data analyze first conductred classical assumption test before hypothesis test. Testing the hypothesis in this study using multiple regression analysis with t-test , f-test and coefficient of determination. The result showed that the coefficient of determination obtained a value 0f 0,399, whitch mean that 39,9 % earning management is affected profitability, ownership of institusional , tax, and good corporate governance quality .Type the balance of 60 , 1 % is influence by other variabels outside the research.Hypotesis test results showed that the profitability, tax, and good corporate governance quality have effect on eraning management ,while the ownership of institusional has not affect on earning management .